An Assessment of How Plant and Mycorrhizal Communities Have Been Affected Along a Mine-Impacted Watershed In The Northwest Territories - MacColl, Kevin (Scholars Commons @ Laurier, 2017)
Giant Mine is an inactive gold mine located nine kilometers north of Yellowknife, Northwest Territories. Giant Mine has been the source of arsenic trioxide for the Baker Creek watershed since it opened over 60 years ago. Although arsenic levels in the creek are above the limits considered to be biologically relevant, there is no concrete evidence that plants and mycorrhizae have actually been affected. This study provides an initial assessment of the impacts mining activity at Giant Mine has had on plants and mycorrhizae in the Baker Creek watershed. Nine sites were sampled around Giant Mine: five sites downstream from Giant Mine along Baker Creek, one site upstream, two nearby wetlands and a distant reference site at Yellowknife River. Sites were distinguished by their level of exposure to the mine; downstream sites were considered the most impacted because they received mine water discharges, therefore having the highest arsenic levels. Two species of plants (Epilobium angustifolium and Phalaris arundinacea) were grown in these soils under laboratory conditions to compare growth responses and mycorrhizal colonization of plants in impacted versus non-impacted soils. A vegetation survey of Baker Creek was also conducted during soil collections in order to determine how patterns in plant species composition differ between sites. Plant roots were also collected to compare levels of colonization among sites to confirm that laboratory results were consistent with those obtained in natural conditions. This study tests the hypothesis that diminished growth and lower mycorrhizal colonization would be observed in plants growing in more impacted soils, and that these results would be reflected in the field through relatively different assemblages of plant species between impacted and non- impacted areas. Results from the growth room study were consistent with this hypothesis. Mean root length of P. arundinacea was 332.99 ± 15.52 cm and 299.75 ± 33.55 cm in soils collected from the upstream site and reference site, ...